Two-pulse sub-ns switching scheme for advanced spin-orbit torque MRAM. (May 2019) - Sverdlov, Viktor; Makarov, Alexander; Selberherr, Siegfried
Highlights: Fast switching of SOT MRAM by two short consecutive orthogonal current pules. Magnetic field free spin-orbit torque switching by the two pulse switching scheme. Switching current reduction by using the two pulse switching scheme. Abstract: The steady increase in performance and speed of modern integrated circuits is continuously supported by constant miniaturization of complementary metal-oxide semiconductor (CMOS) devices. However, a rapid growth of the dynamic and stand-by power due to transistor leakages becomes a pressing issue. A promising way to slow down this trend is to introduce non-volatility in circuits. The development of an electrically addressable non-volatile memory combining high speed and high endurance is essential to achieve these goals. To further reduce the energy consumption, it is essential to replace SRAM in modern hierarchical multi-level processor memory structures with a non-volatile memory technology. The spin-orbit torque magnetic random access memory (SOT-MRAM) combines non-volatility, high speed, and high endurance and is thus suitable for applications in caches. However, its development is still hindered by relatively high switching currents and the need of an external magnetic field for deterministic switching of perpendicularly magnetized layers. The switching by means of two orthogonal current pulses allows achieving deterministic sub-500 ps and magnetic field-free switching in perpendicularly magnetized rectangular structures. Complementing the two-pulse switching scheme with weak perpendicular interface-induced magnetic anisotropy reduces the switching current significantly for achieving sub-500 ps switching in in-plane structures.